Pengaruh Program Pojok Baca Terhadap Kemampuan Membaca Pemahaman Siswa Kelas IV MI SALAFIAH Kota Cirebon - Mohammad Iqfbal Maulana; Syibli Maufur; Inayatul Ummah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The effect of the reading corner program on the reading comprehension ability of grade IV students of MI Salafiah, Cirebon City, Faculty of Teacher Training and Education, UIN Siber Syekh Nurjati Cirebon. This study aims to determine the effect of the reading corner program on students' reading comprehension ability. This type of research is quantitative. The population of the study was all grade IV students of MI Salafiah, Cirebon City, totaling 52 students. In determining the sample, a purposive sampling technique was used, totaling 65 students, so that 27 students of grade IV C and 25 students of grade IV B who were diligent readers. Reading comprehension data were collected by tests and observation results. Data were analyzed using validity test analysis, instrument reliability test, descriptive statistics, prerequisite tests; normality test, homogeneity test, and hypothesis test using the t test. The analysis test was carried out with the help of excel and SPSS 27 for windows. The results showed that there was a significant positive effect with a sig. value of 0.001 <0.05. The reading corner program on reading comprehension of Indonesian in grade IV students at MI Salafiah, Cirebon City.